2013
DOI: 10.1038/onc.2012.641
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionase mediates senescence evasion in melanocytes and melanoma cells

Abstract: The development of malignant melanoma is a highly complex process, which is still poorly understood. A majority of human melanomas are found to express a few oncogenic proteins, such as mutant RAS and BRAF variants. However, these oncogenes are also found in nevi, and it is now a well-accepted fact that their expression alone leads to senescence. This renders the understanding of senescence escape mechanisms an important point to understand tumor development. Here, we approached the question of senescence evas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Consistent with recent findings, we revealed that growth‐promoting signaling pathways, such as E2F targets (Park et al., ), mTORC1 signaling (Damsky et al., ), and MYC targets (Leikam et al., ), are enriched in both young melanocytes and melanomas. Furthermore, a concordant gene expression difference as derived from the senescence model system is found between melanomas and nevi.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with recent findings, we revealed that growth‐promoting signaling pathways, such as E2F targets (Park et al., ), mTORC1 signaling (Damsky et al., ), and MYC targets (Leikam et al., ), are enriched in both young melanocytes and melanomas. Furthermore, a concordant gene expression difference as derived from the senescence model system is found between melanomas and nevi.…”
Section: Discussionsupporting
confidence: 92%
“…47 One widely accepted hypothesis proposes that the accumulation of oxidative damage arising from endogenously produced ROS leads to cellular senescence, tissue degeneration and age-related disorders. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] In contrast, ΔNp63 has a crucial role in maintaining the proliferative potential of epithelial cells and counteracting cellular senescence and organismal ageing. 40,[63][64][65] Therefore, the molecular mechanism through which ΔNp63 exerts its antisenescence/antiageing functions may be mediated, at least in part, by the activation of antioxidant genes, including CYGB.…”
Section: Discussionmentioning
confidence: 88%
“…DATS (25 μM) inhibited growth of both cell types by increasing intracellular ROS generation and cytosolic Ca 2+ mobilization and by decreasing mitochondrial membrane potential without having significant effects on normal keratinocyte HaCaT cell growth. In a more recent study from the same group (Wang, Chu, Hsieh, & Sheen, 2017), DATS (at 10 and 25 μM) Although the antiproliferative effects of increased production of CSE-derived H 2 S were reported, the study from Leikam et al (2014) showed that CSE overexpression in tumour cells had pro-tumorigenic functions and that the blockade of CSE enzymic activity in human melanoma cells not only reduced proliferation rates and enhanced cell sensitivity to H 2 O 2 but also induced senescence. Therefore, the role of CSE-derived H 2 S on tumour regulation cannot be absolutely defined as this may be related to the actual amounts of H 2 S produced by this enzyme in the different cell systems studied, bearing in mind the U-shaped pattern of the dose-concentration-response curves that H 2 S usually shows in many experimental models and systems.…”
Section: Melanomamentioning
confidence: 98%